Corifollitropin Alfa for Controlled Ovarian Stimulation in Assisted Reproductive Technologies: State of the Art - Carvalho, Bruno Ramalho de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Physical and emotional burdens during the journey of infertile people through assisted reproductive technologies are sufficient to justify the efforts in developing patient-friendly treatment strategies. Thus, shorter duration of ovarian stimulation protocols and the need for less injections may improve adherence, prevent mistakes, and reduce financial costs. Therefore, the sustained follicle-stimulating action of corifollitropin alfa may be the most differentiating pharmacokinetic characteristic among available gonadotropins. In this paper, we gather the evidence on its use, aiming to provide the information needed for considering it as a first choice when a patient-friendly strategy is desired.
Keywords: corifollitropin alfa; ovulation induction; ovarian stimulation; gnrh antagonist; assisted fertilization